Away from Nature, Culture becomes Unsustainable. Cultivating Nature - Joaquin García Carrasco (FahrenHouse, 2020)
Objective: To propose and justify a pedagogical initiative that fosters direct contact with nature. Method: Bibliographical search for arguments that show how culture originated in direct contact with the ecosystem, even prior to the deployment of the stone industry and before language competency. Demonstrate that the beginnings of the ecology movement involved denouncing the degradation of the biosphere and propose a sense of amazement as the pillar of Environmental Education. Sources: The scholarly sources used to justify the objective will be interdisciplinary, including international documents that converge on the same point of view. Conclusion: A school garden can be a pedagogical instrument for recovering familiarity with the world of life, providing a context to go deeper into the relations shat link us to other living beings. Eco-literacy is a cultural movement that recommends and values the school garden as an instrument for motivating knowledge and sensitivity in relation to all forms of life.